Introducing electric spring in the voltage frequency regulation of a multi area multi source integrated power system network - Debdeep Saha; Soham Dutta (Scientific Reports)
Abstract The present work demonstrates the application of an electric spring in a multi-source interconnected power system in which coordinated control of frequency and voltage loop is investigated. A two-area power system is considered with non–linearity for the thermal power system, such as generation rate constraint and governor dead band, so that the developed model is realistic. A novel cascade controller, namely a two–degree–of–freedom proportional–integral–derivative controller cascaded with a proportional–integral–derivative controller (2DOFPID–PID), is utilized for the first time for reducing the area control error to zero in both the control areas. A powerful algorithm known as the Golden Jackal Algorithm (GJA) is considered for tuning the controller parameters and achieving the minimum performance index. System dynamic responses are observed for the coordinated automatic load frequency control and automatic voltage regulator during step load perturbations and random load perturbations. Selection of the best performance index (PI) among integral of squared error (ISE), integral of time multiplied by absolute error (ITAE), integral of time multiplied by squared error (ITSE), and Integral of absolute error (IAE) proves that ITAE serves the best among others. To model an AC/DC bus, system responses are also investigated with a parallel AC/DC link that depicts satisfactory results in terms of overshoot, undershoot, and settling time. Modelling of the electric spring in the proposed system is integrated to check the terminal voltage deviation and frequency deviation, and mitigate them. Results show reduced generator terminal deviation in both the control areas. Comparison of different powerful algorithms with the proposed one infers the superiority of the proposed golden jackal algorithm with reference to the performance index vs. number of iterations.